Misconception of Islamic apparel, niqab: a phenomenological approach - Nasrin Akter Chowdhury,; Amani Ali Elmetwally,; Hanif Suhairi Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Communication is a social process in which individuals use symbols to establish and interpret meaning in their environment. Artifact is a valuable source of communication in our historical and everyday life. The Islamic artifacts use in daily life constantly support or contradict our beliefs, values and self identities. Muslim communities have traced the authenticity and legitimacy their customary practices of Islamic attire by the guidance of the Quran and Hadith. The purpose of this qualitative study is to examine and explore the meanings, structures and the essence of the perceived experience of Muslim niqab wearing women within a phenomenological manner. Niqab wearing is women's individual choice and empowerment, and its expression is Islamic identity. Now a days niqab wearing is controversial issue due to misunderstanding among Muslim and non-Muslim community. The goal of this study is to investigate a detailed and comprehensive understanding of the Islamic concept of niqab wearing women. The expected result of this research will contribute to a critical discussion on the rationale of controversy of niqab wearing, especially in the perspective of abuse, and justify women's right in context of Islamic culture based on Quranic obligation that will not create political and cultural discrimination in the society.